Effects of sintering temperature to the mechanical properties and microstructures of Fe 67 Cr 22 Al 11 powder compacts - Rahman M.M.; Namasivayam D.; Rahman H.Y. (Microscopy Society of Malaysia, 2023)
This paper presents an experimental investigation on the effects of sintering temperature to the mechanical properties and microstructures of FeCrAl powder compacts formed through warm powder compaction route. Elemental iron powder ASC 100.29, copper and aluminum powder were blended mechanically in a low speed mixer. The blended powder mass was compacted at a temperature of 200C and was later sintered in an argon gas fired furnace by varying the sintering temperature, i.e., 600C, 750C and 900C for 90 minutes. The sintered products were then subjected to density measurement, flexure strength measurement as well as microstructure analysis through scanning electron microscopy. The results revealed that the suitable sintering temperature is 600C which generated light weight products with higher bending strength, lower volumetric expansion, and better microstructure. 2019, Microscopy Society of Malaysia. All rights reserved.